Assessing the prudential approach of the Financial Services Commission towards corporate failure in Mauritius. Issue 2 (12th March 2018) - Mahadew, Roopanand; Luchmun, Bhavna
Abstract : Purpose: This paper aims to provide a comprehensive overview of the sphere of corporate failure in Mauritius. The causes are explained and urge to take preventive measures is justified therein. Recommendations are finally proposed to prevent corporate failure in Mauritius. Design/methodology/approach: The methodology used is based on a mixture of the legal research method and case study analysis. This paper analyses every legal instrument such as enactments, binding rules, regulations and guidelines relevant to the Financial Services Commission (FSC) and the insurance sector in Mauritius. Findings: The prudential approach by the FSC is on the basis of any attempt for preventing corporate failure in Mauritius. However, there is still room for improvement with amendments that can be brought to various stages, such as the licensing, compliance and regulation stage. Research limitations/implications: In terms of research limitation, this is an area that is quite new in Mauritius, implying that literature would mostly be indirect in nature. However, it has a high implication as it positions itself as one of the first pieces of literature on the issue of corporate failure in Mauritius. It can be the beginning of a long and required series of literature much needed in the field. Practical implications: The effectiveness of the regulatory power of the FSC is essential for the financial sector's future of Mauritius. The amendments that are proposed thought this study would help to immediately improve the health of this essential sector. Social implications: It posits the business world as an area in which the social impacts are significant. The social implications would be towards researchers, students, practitioners and policymaker. Also, it is a piece of research that would be important for investors who would want to invest in the financial sectors in Mauritius. Originality/value: This paper will be highly instrumental to policymakers, regulatory authorities, international investors and local businessmen wishing to enter the financial services sector to have a better idea of how this very important pillar of the economy of Mauritius can be shielded better against failure and how it can be enhanced to promote the economic growth of Mauritius.